Depression Levels of State Functionaries: Empirical Evidence From China - He, Li; Wang, Kun; Zhang, Zixian; Wang, Jiangyin; Li, Tianyang; Wang, Yuting; Yang, Lixingzi; Wu, Yuanyang; Zhang, Shuo; Zhang, Siqing; Yang, Hualei (Frontiers in Psychiatry, 2021)
This study aimed to explore the depression levels of those serving as state functionaries in China. We used data from the 2016 China Labor-force Dynamics Survey and the ordinary least squares model for the regression analysis. The results found: i) The degree of depression of state functionaries was found to be lower than that of other workers; that is, the overall depression index of state functionaries was 1.010 points lower, and the result was significant at the degree of 1%; ii) state functionaries had a lower degree of depression than workers in all other occupation groups; iii) older state functionaries had lower depression than their younger counterparts; iv) the degree of depression of state functionaries in the provinces involved in China's three major urban agglomerations was higher than that of those in other provinces; and v) the degree of depression of female state functionaries was lower than that their male peers. Thus, there is an association between serving as a state functionary in China and depression. State functionaries have lower levels of depression than other working groups. These levels were generally lower but varied according to age, sex, and province.